(3dhGYL GdZQGes - (3YHO GdeYjf Hf CMeO Hf CHj GdaJM GdHdNj GdMfaj, HGdeYQha HGHf GdnHqcGA,J (B1040 (3g` s ((3eMeO Hf YHOGddg GdOfhTQj GdCTYQj s)
(3ChdgG (B:s
(3hHYO(B' (3aEfj deG QCjJ GdOgQ cGdcGSO jHMK Yf cd QRjI s
(3BNQgG (B:s
(3hGYde Cf GdBf Bf Cf ojMHS ef Gdbde GdYfGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B178s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B171 s
Keywords: (3GdCOHs